Polish Delegations in Kazakhstan During the Second World War: Alma-Аtа and Semipalatinsk - Mara Sh. Gubaidullina; Laura T. Issova; Almagul T. Kulbayeva (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2020)
Introduction. The article investigates the versatile activities of Polish diplomats on the example of the representative offices of the embassy of Poland (delegations) in Alma-Ata (Almaty) and Semipalatinsk (Semey). Documents in the Kazakhstani archives indicate the presence of nine delegations created during the war in Kazakhstan to facilitate the formation of the Polish army (Anders Army). Polish “delegates” – diplomats, military, civilian employees – helped to rescue the Poles from places of detention and settlements, to draw up their documents for further sending to the army.